2022
DOI: 10.1111/nmo.14418
|View full text |Cite
|
Sign up to set email alerts
|

A novel scalable electrode array and system for non‐invasively assessing gastric function using flexible electronics

Abstract: Background: Disorders of gastric function are highly prevalent, but diagnosis often remains symptom-based and inconclusive. Body surface gastric mapping is an emerging diagnostic solution, but current approaches lack scalability and are cumbersome and clinically impractical. We present a novel scalable system for non-invasively mapping gastric electrophysiology in high-resolution (HR) at the body surface. Methods:The system comprises a custom-designed stretchable high-resolution "peel-and-stick" sensor array (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
162
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(163 citation statements)
references
References 55 publications
1
162
0
Order By: Relevance
“…39 Previous work has also demonstrated that an amplitude increase in response to a meal is a normal feature of cutaneous gastric recordings, with ff-AR metrics previously commonly employed in EGG studies, albeit over substantially shorter time periods. 10,[20][21][22] However, we noticed that many healthy controls demonstrate high fasting baseline amplitude at the gastric frequency, such that the perceived meal response is diminished or absent. This finding could be due to cephalic-phase gastric activity, 40 migrating motor complex activity, 41 or circadian variations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…39 Previous work has also demonstrated that an amplitude increase in response to a meal is a normal feature of cutaneous gastric recordings, with ff-AR metrics previously commonly employed in EGG studies, albeit over substantially shorter time periods. 10,[20][21][22] However, we noticed that many healthy controls demonstrate high fasting baseline amplitude at the gastric frequency, such that the perceived meal response is diminished or absent. This finding could be due to cephalic-phase gastric activity, 40 migrating motor complex activity, 41 or circadian variations.…”
Section: Discussionmentioning
confidence: 99%
“…8 BSGM employs a dense grid of electrodes to non-invasively map gastric activity in high-resolution at the epigastrium, registering the myoelectrical activity that coordinates gastric motility and peristaltic activity through an increase in signal strength. 9,10 BSGM represents a critical advance over traditional electrogastrography (EGG) approaches due to a combination of technical improvements that serve to maximally extract the weak underlying gastric signals while minimizing contamination by noise. These features include a high-resolution (HR) array of large area that accounts for gastric anatomical biodiversity while allowing signal summation from multiple sites, bioelectronics and signal processing systems specifically optimized for gastric electrophysiology, and a robust validated artifact detection and rejection scheme.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations